OP0067 Usefulness of the basal and pilocarpine-stimulated salivary flows in primary sjÖgren's syndrome. (1st June 2001) - Rosas, J; Ramos-Casals, M; Ena, J; Garcia-Carrasco, M; Verdu, J; Cervera, R; Font, J; Caballero, O; Ingelmo, M; Pascual, E
Abstract : Background: Objectives: To examine salivary function in patients with primary Sjögren's syndrome (SS) by assessing unstimulated and stimulated flows using a 2% pilocarpine solution. Methods: We investigated the clinical and immunological characteristics of 60 consecutive patients with primary SS. All patients fulfilled four or more of the preliminary diagnostic European criteria for SS. We measured unstimulated (basal) salivary flows (BSF) in all patients. In those patients with a BSF < 1.5 mL, stimulated salivary flows (SSF) were also measured after the stimulus with an ophthalmic 2% pilocarpine solution. Results: Of the 60 patients, 55 were women and 5 men, with a mean age at the SS onset of 61 years (range 18 to 82 years). The mean BSF for SS patients was 1.40 ± 0.17 mL. Fifty (83%) patients showed a BSF less than 1.5 mL. No clinical or immunological differences were found between SS patients with BSF more or less than 1.5 mL, although those patients with a BSF less than 1.5 mL showed more frequently a parotid scintigraphy class III or IV (42% vs 0%, p = 0.01). Finally, those SS patients with a pilocarpine-SSF less than 1.5 mL showed a higher time of SS evolution (73.3 vs 31.3 months, p = 0.03) and a higher prevalence of positive anti-Ro/SS-A (70% vs 36%, p = 0.038), anti-La/SS-B (65% vs 32%, p = 0.038), parotid scintigraphy class III-IV (79% vs 9%, p < 0.001) and positive salivary gland biopsy (90% vs 43%, p < 0.001). Conclusion: The study of xerostomia using basal and pilocarpine-stimulated salivary flows are methods simple to perform and acceptable to patients with no special equipment. Twenty-two of the 46 patients with low BSF obtained stimulated flows over 1.5 mL These "responders" patients showed a lower time of evolution of sicca symptomatology, a lower frequency of positive immunological markers and milder grades of scintigraphic patterns and lymphocytic infiltrates on salivary gland biopsies.